Synthesis, DNA-binding and antiproliferative properties of diarylquinolizinium derivatives. Issue 4 (7th January 2021) - Bortolozzi, Roberta; Ihmels, Heiko; Schulte, Robin; Stremmel, Christopher; Viola, Giampietro
Abstract : Diaryl-substituted quinolizinium derivatives constitute a promising class of readily available DNA binding and cytotoxic compounds with a relatively strong antiproliferative effect on selected tumor cells. Abstract : A series of ten 2, 7- and 2, 8-diarylquinolizinium derivatives was synthesized and their DNA-binding and cytotoxic properties were investigated. Except for one nitro-substituted derivative all tested diarylquinolizinium ions bind to DNA with sufficient affinity (2 × 10 4 M −1 –2 × 10 5 M −1 ). It was shown with photometric, fluorimetric and polarimetric titrations as well as with flow -LD analysis that the ligands bind mainly by intercalation to duplex DNA, however, depending on the ligand–DNA ratio, groove binding and backbone association were also observed with some derivatives. The biological activity was further investigated with tests of cytotoxicity and antiproliferative properties towards non-tumor cells and selected cancer cells, along with cell cycle analysis and an annexin-V assay. Notably, substrates that carry donor-functionalities in the 4-position of the phenyl substituents revealed a strong, and in some cases selective, antiproliferative activity as quantified by the growth inhibition, GI50, at very low micromolar and even submicromolar level both in leukemia and solid tumors.